Guest Editors' Introduction: Ethics, Corporate Social Responsibility, and Developing Country Multinationals. Issue 3 (July 2016) - Doh, Jonathan; Husted, Bryan W.; Yang, Xiaohua
ABSTRACT: In this article we provide an overview of the literature on ethics and social responsibility of developing country multinationals (DMNEs) and an introduction to the contributions of the articles in this special section. With the rising influence of DMNEs in the global economy, there is increasing interest in applying descriptive, explanatory, and normative theories to understand the ethics and CSR behavior and practices of DMNEs. This article provides an overarching review of perspectives first from ethics, CSR, and business and society, and then from international business and management scholarship. We identify limits and gaps in the current literature and show how the articles in our special section contribute to fill these gaps. We highlight the emerging, transitional and distinct features of DMNEs that are different from their domestic and foreign counterparts. The very limited extant literature and the contributions of this special section underscore the influence of institutional voids and duality that appear to prompt DMNEs to pursue CSR as a signaling mechanism to gain legitimacy, overcome liabilities of foreignness and obtain a "license to operate" in developed countries. We outline the key contributions from the articles in this special section and discuss the future research agenda espoused by the issues raised in these articles.